SISTEM INFORMASI PENJADWALAN MENGAJAR MENGGUNAKAN METODE ALGORITMA GENETIKA PADA SMK 10 NOPEMBER JOMBANG - Suprayitno/mak Yunus Suprayitno/amak yunus (Fakultas Sains dan Teknologi, 2015)
ABSTRACTSuprayitno, Parsun. 2014. Teaching Sheduling Information System Using Genetic Algorithms in SMK 10 Nopember Jombang. Department of Information System, Faculty of Information Technology Kanjuruhan University of Malang. Preceptor: Amak Yunus, S.Kom, M.Kom.Keyword : Information System, Scheduling , Genetic Algorithm.Scheduling process at SMK 10 November Jombang is to combine the components of teachers, subjects, classes and time. There are schedules conflict as well as the problem of teachers demands not be able to teach at a particular time. It is necessary to build scheduling information system using Genetic Algorithm, which simulates the process of evolution to produce the chromosomes of each population randomly, then chromosomes replicate in accordance to laws of evolution be tranformated into prime chromosome. This chromosome produces a solution of the issues raised.The conclusion of this system; it can arrange the overall timetable, schedule conflicts can be resolved and demand of teachers not be able teach on certain days and hours can be fulfilled